Progress in fabrication of second generation high temperature superconducting tape at Shanghai Superconductor Technology. (25th February 2019) - Zhao, Y; Zhu, J-M; Jiang, G-Y; Chen, C-S; Wu, W; Zhang, Z-W; Chen, S K; Hong, Y M; Hong, Z-Y; Jin, Z-J; Yamada, Y
Abstract: The development and application of second generation high temperature superconducting (2G-HTS) tapes have attracted much attention in China recently. Progress in upscaling high performance 2G-HTS tape production at Shanghai Superconductor Technology (SST) is reported in this paper. With ion beam assisted deposition, biaxially textured buffer layers with a configuration of CeO2 /LaMnO3 /MgO/Y2 O3 /Al2 O3 /C-276 have successfully been fabricated. In-plane and out-of-plane texture degrees of CeO2 films achieve 2°–4° and 2°, respectively. A multi-plume multi-turn pulsed laser deposition (PLD) system combined with the so-called 'radiation assisted conductive heater' has been proposed and further developed for REBCO layer deposition. Our effort was focused on minimizing the temperature variations in the deposition region by modifying the heating shield that assists the conductive heater of the drum-like cylinder. A tape travelling speed of 100–180 m h −1 can be achieved with a steady temperature profile when passing through the deposition zone, which is very beneficial for the growth of the REBCO layer. Taking advantage of the liquid phase growth mode, several compositions of superconducting films with a thickness in the range of 1–2.5 μ m have been grown with high growth rates of over 40 nm s −1 . Furthermore, the microstructures and superconducting performance were investigated in detail. Based on these studies, superconducting tapes with piece lengths of up to 500 meters have been developed. High I c values at 77 K, self-field (over 520 A cm −1 width) or at low temperature, high magnetic field conditions (over 560 A/4 mm width at 4.2 K, 10 T, perpendicular field) have been achieved. Lamination and jointing techniques have also been developed by SST for power and magnet applications.